Clipping on Crossed Wrapping Method for Ruptured Blood Blister-Like Aneurysm of the Internal Carotid Artery: Technical Note and Long-Term Results - Nishi, Toru (World Neurosurg X, 2019)
BACKGROUND: We have been performing the clipping on crossed wrapping (COCW) method using 2 strips of cotton on patients with an internal carotid artery blood blister-like aneurysm (IC-BLA). This method is reliable in preventing the clips from slipping off and the aneurysm walls from being damaged during clipping, and it enables more appropriate and safer clipping. Here we report the technical details of this method and the long-term outcomes of patients receiving this procedure. METHODS: Fifteen of 1275 (1.5%) patients with a ruptured cerebral aneurysm who received treatment at the Saiseikai Kumamoto Hospital during the period from January 1, 1999, to December 31, 2016, had an IC-BLA. All 15 patients were treated with COCW, except for the first patient, who was treated using a single strip of cotton. The long-term outcome of the treatment was analyzed. RESULTS: The mean follow-up period was 74 months. The first patient experienced rerupture of an aneurysm 10 days after the operation. No complications or regrowth of an aneurysm were observed in the remaining 14 patients during the follow-up period, except for 1 patient who received a reoperation for the regrowth of an aneurysm. As the final outcome, the numbers of patients with a Modified Rankin Score of 0, 3, and 6 were 13, 1, and 1, respectively. CONCLUSIONS: It is suggested that COCW is a treatment that enables safe and long-term management of lesions in IC-BLAs.